Functional relationship between material property, applied frequency and ozone generation for surface dielectric barrier discharges in atmospheric air - Sherlie Portugal (Nature Portfolio, 2017)
Abstract We report the experimental characterization of ozone generation in dielectric barrier discharges as a function of the material and characteristics of the dielectric barrier, operating frequency and the power consumed by a surface DBD-plasma reactor in air at atmospheric pressure. To identify the effect of the dielectric barrier, ozone production curves corresponding to ten dielectric barriers with different effective thicknesses and thermal properties are compared and analyzed for two combinations of voltage amplitudes and frequencies: 7 kV/10 kHz and 8.5 kV/14 kHz. The influence of the operating frequency over the ozone generated by a DBD-plasma reactor is studied by varying the frequency in the range 8–20 kHz. The correlation between power measurements and ozone concentrations as well as ozone quenching effects at extreme power conditions are also discussed.